TINJAUAN SOSIOLOGIS TERHADAP FENOMENA PENCURIAN BARANG DI KONTRAKAN UNGU JALAN GARUDA SAKTI, KECAMATAN BINAWIDYA, KOTA PEKANBARU - kartika, Putriana Kartika Wulandari; Ralinsi, Layyina Ralinsi; Aura, Arilianti Aura Rabi'ah Zaukhan; Aprilia, Auliani Aprilia; Rahmatullaila, Fitri Rahmatullaila; Hambali, Hambali; Junita Fransisca; Luthfi Aisyah Hasibuan; Chika Zaffa Azzahira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze in depth the social problems related to the increasing number of theft cases in Garuda Sakti, especially in the Ungu Rental located on Jalan Garuda Sakti, Bina Widya District, Pekanbaru City. This area is known as a rental housing for students from various regions, making it vulnerable to crime. This phenomenon is studied because it illustrates the social problems that arise due to economic problems and low security in the Garuda Sakti area. Based on the findings of the study, the importance of maintaining the community's living environment and the importance of economic improvement. Therefore, this study is expected to contribute to the community and increase social awareness of security in the Garuda Sakti area.